The Epidemiology of HIV Among People Born Outside the United States, 2010-2017. (September 2020) - Kerani, Roxanne P.; Satcher Johnson, Anna; Buskin, Susan E.; Rao, Deepa; Golden, Matthew R.; Hu, Xiaohong; Hall, H. Irene
Objective: Although some studies have reported a higher incidence of HIV infection among non–US-born people than among US-born people, national data on this topic are scarce. We compared the epidemiology of HIV infection between US-born and non–US-born residents of the United States and examined the characteristics of non–US-born people with diagnosed HIV infection by region of birth (ROB). Methods: We used a cross-sectional study design to produce national, population-based data describing HIV infection among US-born and non–US-born people. We analyzed National HIV Surveillance System data for people with HIV infection diagnosed during 2010-2017 and reported to the Centers for Disease Control and Prevention (CDC). We compared data on demographic characteristics, transmission risk category, and stage 3 infection (AIDS) classification within 3 months of HIV diagnosis, by nativity and ROB. Results: During 2010-2017, 328 317 children and adult US residents were diagnosed with HIV infection and were reported to CDC: 214 973 (65.5%) were US-born, 50 301 (15.3%) were non–US-born, and 63 043 (19.2%) were missing data on country of birth. After adjusting for missing country of birth, 266 147 (81.1%) people were US-born and 62 170 (18.9%) were non–US-born. This group accounted for 15 928 of 65 645 (24.2%) HIV diagnoses among girls and women and 46 242 of 262 672 (17.6%) HIV diagnoses among boys and men. A larger percentage of non–US-born people than US-born people had stage 3 infection (AIDS) at HIV diagnosis (31.2% vs 23.9%). Among non–US-born people with HIV diagnoses, 19 876 (39.5%) resided in the South. Conclusions: Characterizing non–US-born people with HIV infection is essential for developing effective HIV interventions, particularly in areas with large immigrant populations.